2011
DOI: 10.1021/bc200175c
|View full text |Cite
|
Sign up to set email alerts
|

High-Yielding Aqueous 18F-Labeling of Peptides via Al18F Chelation

Abstract: The coordination chemistry of a new pentadentate bifunctional chelator (BFC), NODA-MPAA 1, containing the 1,4,7-triazacyclononane-1,4-diacetate (NODA) motif with a methyl phenyl acetic acid (MPAA) backbone, and its ability to form stable Al18F-chelates, was investigated. The organofluoroaluminates were easily accessible from the reaction of 1 and AlF3. X-ray diffraction studies revealed aluminum at the center of a slightly distorted octahedron, with fluorine occupying one of the axial positions. The tert-butyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
153
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 44 publications
(97 reference statements)
10
153
1
Order By: Relevance
“…This novel technique has been successfully applied to several peptides, including a GRPR agonist (28) and recently to GRPR antagonists (31,32). Recently, McBride et al reported the labeling of peptides with Al 18 F in a 1-pot, 1-step procedure using the NODA-MPAA chelator (26,33), leading to a kit formulation, after which the labeled peptide could be purified by solid-phase extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel technique has been successfully applied to several peptides, including a GRPR agonist (28) and recently to GRPR antagonists (31,32). Recently, McBride et al reported the labeling of peptides with Al 18 F in a 1-pot, 1-step procedure using the NODA-MPAA chelator (26,33), leading to a kit formulation, after which the labeled peptide could be purified by solid-phase extraction.…”
Section: Discussionmentioning
confidence: 99%
“…JMV5132 was synthesized in the same manner as JMV4168 but was coupled to tert-butyl (tBu)-protected NODA-MPAA instead of tBu-protected DOTA. NODA-MPAA was prepared as previously described using NO2AtBu (Chematech) (26). The chemical structures of JMV4168 and JMV5132 are shown in Figure 1.…”
Section: Synthesis Of Jmv4168 and Jmv5132mentioning
confidence: 99%
“…This process requires a long synthesis time of approximately 2 h. We were able to radiolabel Affibody molecules with 18 F within 30 min using a 2-step, 1-pot reaction. In addition, in future studies the specific activity of 18 F-NOTA-Z HER2:2395 may be improved by using different chelators and solvents (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…As shown previously, NOTA-conjugated peptides can be labeled with 18 F using the Al 18 F method (17)(18)(19). Here, we describe the 18 F labeling of NOTA-8-Aoc-BBN(7-14)NH 2 , using the new 1-pot, 1-step, labeling method.…”
mentioning
confidence: 91%